Announcement Effects of Unconventional Monetary Policies on Portfolio Flows to Hong Kong - Lam, Rex (Columbia Undergraduate Research Journal, 2014)
As the Federal Reserve continues its bond purchases to support the economy, the spillover effects created by unconventional monetary policies in the U.S. have garnered more attention. In particular, there is a need to better understand hot money and to determine whether unconventional bond purchases have played a role in increasing capital flows to emerging markets. Since former Federal Reserve Chairman Ben Bernanke’s testimony, weekly equity fund flow out of emerging markets has averaged a staggering $3.4 billion 1. Although it is unclear whether such rapid outflow has negative consequences on economies, policymakers must make every effort to end unconventional purchases with minimal damage on the financial stability of the global economy. As an important financial center in the Asia Pacific region, Hong Kong is an interesting case to study because of its currency peg to the USD and the possibility that investors use Hong Kong as an entry point to China and other emerging and developing economies in that region. If the latter point were true, examining portfolio flows to Hong Kong would be an essential step towards understanding whether unconventional monetary policies have changed the nature of portfolio flows to emerging markets in Asia and whether these flows have brought about booms in local markets.